The impact of regular training programme on the speed and agility performance of the young football players - Sermaxhaj, S. (Sport Science - International Scientific Journal of Kinesiology, 2017)
Training programs for young soccer players have meant the optimal development of relevant performance for the game of football. In recent decades we have evolution of different programs for preparing the players during different time periods of their development. The objective of this research is to prove the impact of the training program on a macro cycle (preparatory period and the period of the championship races) in speed and agility performance of young players. The research was conducted between August and November 2015 with a sample of 22 young soccer players divided into two groups (10 players range 11-13 years and 12 players range 13-15 years). At first have been measured initialled body weight and body height, speed (5m, 10m, and 30m) and agility (5x10m, 20m zigzag with and without ball). Speed and Agility was measured with electronic photocells`, with measure of .01 sec. Two groups of players have conducted a regular program of training 3 times a week for a period of 4 months. After completing the regular program of training, participants in both groups underwent final measurements. Results of paired sample t-test analysis have shown that the regular program training have impacted on statistically significant differences between the two tests (initial and final) in the variables of speed and agility of young soccer players (11-13 year old range), but not important statistical values of young soccer players (13-15 year old range). The level of significant is p<.05. From the collected results we can conclude this regular training program has an important statistical impact in the speed and agility of the young football players (11-13 year old range) and no important statistical impact on the young football players (13-15 year old range). From this we can conclude that age is 11-13 years of age when speed and agility have a more rapid development.